The Influence of Transformational Leadership, Organizational Culture, and Organizational Commitment on Innovative Work Behavior in Employees of PT. Herba Emas Wahidatama, Purbalingga Regency - Gemasari, Agustin Putriyana; Endratno, Hermin; Widhiandono, Hengky; Rahmawati, Ika Yustina (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research aims to determine the influence of Transformational Leadership, Organizational Culture, and Organizational Commitment on Innovative Work behavior at PT Herba Emas Wahidatama. The population in this study was 108 employees of PT Herba Emas Wahidatama employees, with a research sample of the entire population. This type of research is a quantitative method. Questionnaires were distributed in December-January. The primary data is used using the saturated sampling method. Instrument test: reliability test, classic assumption test: normality test, multicollinearity test, and heteroscedasticity test. The next tests are the model suitability test, multiple regression analysis, partial t- test, and the determinant coefficient R2 using the SPSS data analysis tool 26. The results of the study that have been obtained show that transformational leadership affects innovative work behavior, organizational culture does not affect innovative work behavior, and organizational commitment has no effect on innovative work behavior.